PRELIMINARY ANTIMICROBIAL SCREENING OF LEAF EXTRACT OF COSTUS IGNEUS USING ETHANOL EXTRACT - Benila S,; Ragel Mabel Saroja R, (The Bioscan, 2025)
Costus igneus, also known as the “insulin plant,” is a widely recognized medicinal plant in Indian traditional medicine, particularly for its role in managing diabetes and other metabolic disorders. This study explores the antimicrobial potential of Costus igneus, focusing on its ethanol extract derived from the leaves. The ethanol extract was tested for its antibacterial and antifungal activities using the agar well diffusion method against various microbial pathogens, including Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, Aspergillus flavus, Aspergillus niger, and Aspergillus terreus. Results indicated significant antibacterial activity, particularly against Gram-positive bacteria, with zones of inhibition ranging from 10 mm to 25 mm. The antifungal activity showed an inhibition range of 10 mm to 14 mm, with Aspergillus niger being most susceptible to the extract. The study also compared the effectiveness of Costus igneus extracts to standard antibiotics (streptomycin and fluconazole), revealing comparable inhibitory effects. The findings suggest that Costus igneus, with its bioactive compounds, has considerable antimicrobial potential, making it a promising candidate for developing alternative antimicrobial agents. These results further validate its medicinal significance in folk medicine and open pathways for future research into plant-based antimicrobial agents.